The Chang Gung Research Database—A multi‐institutional electronic medical records database for real‐world epidemiological studies in Taiwan - Shao, Shih‐Chieh; Chan, Yuk‐Ying; Kao Yang, Yea‐Huei; Lin, Swu‐Jane; Hung, Ming‐Jui; Chien, Rong‐Nan; Lai, Chi‐Chun; Lai, Edward Chia‐Cheng (Pharmacoepidemiology and drug safety, 2019)
Purpose The Chang Gung Research Database (CGRD), the largest multi‐institutional electronic medical records (EMR) collection in Taiwan, provides good access for researchers to efficiently use the standardized patient‐level data. This study evaluates the capacity and representativeness of the CGRD to promote secondary use of EMR data for clinical research with more accurate estimates. Methods The National Health Insurance Research Database (NHIRD) which covers over 99.9% of the Taiwanese population served as the comparator in this study. We compare the data components of the CGRD with the NHIRD, including records for health care facilities, patients, diagnoses, drugs, and procedures. Using the chi‐square test, we compared the distributions of age categories and sex of patients, and the rates of their health conditions between NHIRD and CGRD based on the year 2015. Results The CGRD contains more clinical information such as pathological and laboratory results than the NHIRD. The CGRD includes 6.1% of outpatients and 10.2% of hospitalized patients from the NHIRD. We found the CGRD includes more elderly outpatients (23.5% vs 12.5%) and pediatric inpatients (19.7% vs 14.4%) compared with the NHIRD. We found patients' sex distributions were similar between CGRD and NHIRD, but coverage rates of severe conditions, such as cancer, were higher than other health conditions in CGRD. Conclusions The CGRD could serve as the basis for accurate estimates in medical studies. However, researchers should pay special attention to selection biases since patients' characteristics from CGRD differ from those of the national database.